The Species of the mali-Group of Aphelinus (Hymenoptera: Aphelinidae), with Descriptions of Three New Species, DNA Sequence Data and One Newly-Recorded Species from China - Zhigang Dong; Ye Luo; Junqing Ge; Jian Huang; Andrew Polaszek; Zhuhong Wang (Insects)
Seventeen species of the mali-group of Aphelinus (Hymenoptera: Aphelinidae) are reviewed worldwide, including three new species, and five previously described species in China. The mali-group was defined by a combination of characters: head and body dark with parts of metasoma pale; fore wing with a complete row of setae inside the linea calva, or also only with a few setae in the angle between the linea and marginal vein; legs with mesocoxae, metacoxae and metatibia dark, metafemur pale. In this paper, three new species, Aphelinus tuberocephalus Wang & Huang, sp.n., Aphelinus hainanensis Wang & Huang, sp.n. and Aphelinus ruellia Wang & Huang, sp.n., are described and illustrated, with notes on one species, Aphelinus coreae Hopper & Woolley, new to China. A revised key to species of the mali-group is provided. Mitochondrial (COI) partial sequences were obtained successfully for A. tuberocephalus, A. hainanensis, A. ruellia and A. coreae.